[76] Hereditary kidney stones: An experience of a nephrology department - Hayet Kaaroud (Taylor & Francis Group, 2018)
Objective: To determine clinical and metabolic characteristics and progression of hereditary urinary lithiasis. Genetic factors must be considered in the aetiological diagnosis of urinary lithiasis. Methods: A retrospective study was conducted between 2008 and 2018, and 53 patients were included. Patients were referred to our department for aetiological investigation in 36 cases, for chronic renal failure in eight cases, and from paediatric departments to be followed-up in adulthood in nine cases. Results: In all, 32 men and 21 women were enrolled in this study with a male/female sex ratio of 1.52. The mean (range) age at the time of diagnosis of the hereditary character of the urinary lithiasis was 29 years (4 days–63 years).The mean (range) delay between the onset of the lithiasis disease and the aetiological diagnosis was 10.5 (1–42) years. We noted 26 cases of cystinuria, 17 cases of primary hyperoxaluria type 1 with two mutations (I244T in 15 cases and 33–34 Insc in two cases), and 10 cases of renal tubulopathy. In all, 14 patients had chronic renal failure, of which five were in end-stage. Crystalluria was positive in 62% of the cases. The morpho-constitutional analysis of stones was conducted in 31 cases; oxalo-dependent lithiasis was identified in nine cases and cystine lithiasis in 22 cases. After a mean follow-up of 82 months for 43 patients, we noted normal renal function in 21 cases, chronic renal failure in 12 cases, and haemodialysis in nine cases, all with primary hyperoxaluria and transplantation in one case. Conclusion: The aetiological diagnosis of hereditary urinary lithiasis was made with considerable delay. Cystinuria was the most frequent aetiology and primary hyperoxaluria was the most serious affliction.